TRANSFER RASA DALAM KOMUNIKASI BAHAGIA: KUNCI MEMBANGUN HUBUNGAN POSITIF - Wahyu Rezeki Wahyu Rezeki; Indah Rastika Sari (Jurnal Komunikasi dan Media, 2025)
Happy communication is a crucial aspect of building harmonious interpersonal relationships, where emotional transfer plays a role in effectively conveying and receiving emotions. This study employs a literature review method to analyze how emotional transfer in communication enhances social connectedness and individual psychological well-being. The findings reveal that happiness-infused communication contributes to improved relationship quality across various contexts, including family, workplace, and education. The emotional contagion phenomenon explains how emotions spread from one individual to another, fostering a more positive social environment. However, challenges such as differences in emotional perception and cultural factors can affect the effectiveness of happy communication. Therefore, increasing emotional awareness and communication skills is essential to optimize emotional transfer in communication.